Bronchiectasis. (May 2020) - Johnson, Chris; Haworth, Charles
Abstract: Bronchiectasis is clinically defined as irreversible airways dilatation associated with chronic airway inflammation and infection. It is a cause of chronic cough and recurrent lower respiratory tract infections. The prevalence of diagnosed bronchiectasis is probably increasing as a result of an ageing population and the increased use of radiological investigations. The diagnosis is secured by high-resolution computed tomography of the chest, which should prompt investigation for one of the many underlying causes. These can be identified in up to 65% of patients and, when found, can significantly alter management. The pathogenesis of bronchiectasis is best understood as a vicious cycle of inflammation and infection. Although clinical trial data are often lacking, there are many treatment options that target each of the steps within this cycle. These include the use of airway clearance techniques, mucoactive agents, anti-inflammatories and antibiotics, for both exacerbations and prophylaxis, and in some circumstances bacterial eradication. This intensive approach is necessary as there is considerable morbidity, mortality and health economic cost associated with the condition. However, patient adherence to such complex and long-term treatment can be difficult. This article discusses the epidemiology, pathogenesis, diagnosis and management of bronchiectasis.